Balancing COVID-19 preparedness and 'business as usual' in hospitals: lessons from executives in China, Norway and the UK. Issue 2 (23rd October 2020) - Ikram, Umar; Ren, Hui; Shields-Zeeman, Laura; Frich, Jan; Northam Jones, Daniel; Wu, Jiong; Kuang, Ming; Liu, Yuanli; Ma, Jing
Abstract : Background: During the first wave of COVID-19 pandemic, hospitals were forced to cancel or postpone non-COVID-19 care. With new outbreaks emerging, hospitals are now figuring out how to balance preparedness for future COVID-19 waves with their elective and regular services. This report discusses how four hospital systems deal with these dual responsibilities in China, Norway and the UK. Reflections: Based on the experiences and combined reflections of hospital executives, we have formulated five strategic and leadership lessons for hospitals as they manage these dual responsibilities. (1) Redesign organisation to separate COVID-19 and non-COVID-19 services both within and across hospitals. (2) Expand virtual care strategies to improve access. (3) Use data-driven models to allocate resources across COVID-19 and non-COVID-19 units. (4) Invest in programmes to promote frontline staff well-being. (5) Secure financial support to continue to deliver on the dual responsibilities. Conclusion: The COVID-19 pandemic gives rise to leadership challenges that have fuelled organisational change and new approaches to healthcare delivery. Leading hospitals during the pandemic is a balancing act—providing care for both patients with COVID-19 and non-COVID-19, while at the same time preparing for the next waves of the pandemic.